Colloquial Spanish of Latin American : - Rodriguez-Saona, Roberto (Routledge, 2004)
Colloquial Spanish of Latin America 2 is designed to help those involved in self-study. Structured to give you the opportunity to listen to and read lots of modern, everyday Latin American Spanish, it has been developed to work systematically on reinforcing and extending your grasp of the grammar and vocabulary.